Such a perfect wife [large type] : a novel - White, Kate, 1950- (White, Kate, 1950- Bailey Weggins mystery, 2019)
On a sunny fall morning, Shannon Blaine sets off on a jog along the rural roads near her home in Lake George, New York. It's her usual routine after dropping the kids off at school ... except on this day she never returns. The residents in the idyllic town are stunned. Could Shannon have just taken off, overwhelmed with the pressures of being the perfect wife and mother? Did a stranger snatch her? Or is her husband responsible? The hot new online magazine Crime Beat calls Bailey Weggins to cover the case, and it doesn't take long for her to see that it has far more suspects than she initially realized: a bitter sister, an unfaithful brother-in-law, an evasive deacon, and a creepy local motel owner. When an anonymous caller reaches out to Bailey with the cryptic clue that Shannon was a "good Catholic girl," it leads Bailey to the grisly discovery of the missing woman's body-but, stunningly, other bodies are there alongside hers.